Aquatic macroinvertebrate diversity and composition in streams along an altitudinal gradient in Southeastern Brazil - Henriques-Oliveira, Ana Lucia; Nessimian, Jorge Luiz (Biota Neotropica, 2010)
Aquatic macroinvertebrate diversity and composition in streams along an altitudinal gradient in Southeastern Brazil. A study concerning taxonomic richness and composition of the aquatic insect fauna in streams within the same catchment basin along an altitudinal gradient in Southeast Brazil, was conducted to test the hypothesis that there is a faunal discontinuity in the biocenotic composition, related to differences in altitude and latitude. In Southeastern Brazil, around latitude 22°, this faunal transition from rhithron to potamon biocenosis should occur at 500 m above sea level. Eighteen tributaries of the Mambucaba River, at Serra da Bocaina National Park, SP-RJ, Brazil, were studied. The streams were separated into 6 altitudinal zones (zone 1: above 1500 m; zone 2: 1200-1300 m; zone 3: 900-1000 m; zone 4: 400-700 m; zone 5: 100-300 m; and zone 6: 0-100 m) each including three streams. The aquatic insects were identified at the lowest possible taxonomic level. The highest richness was observed in altitudes between 1200-1300 m, while the lowest occurred in altitudes below 100 m. The Indicator Value method indicated taxa characteristic for four of the six altitudinal zones considered in this paper. Sorensen's Index and CCA results showed that distribution and composition of aquatic insect fauna of Serra da Bocaina National Park was influenced primarily by altitude and temperature rather than stream size. The absence of indicator species and the lower abundance in altitudes between 400-700 m suggest a transition from rhithral to potamal fauna, which is distinct at 200 m.